Dialogicity in written specialised genres - Gil Salom, Luz; Soler-Monreal, Carmen (Dialogue studies ;, 2014)
Dialogicity in Written Specialised Genres analyses how human beings intentionally establish a network of relations that contribute to the construction of discourse in different genres in academic, promotional and professional domains in English, Spanish and Italian. The chapters in the present volume investigate individual voices, both those assumed by the writer and those attributed to others, and how they act interpersonally and become explicit in the discourse. From a number of different research approaches, contributing authors focus on various textual components: self-mention, impersonation, attribution markers, engagement markers, attitude markers, boosters, hedges, reporting verbs, politeness strategies and citations. The collection is unusual in that it addresses these issues not only from the perspective of English, but also from that of Spanish and Italian. It thus represents a refreshing reassessment of the contrastive dimension in the study of voice and dialogic relations, taking into consideration language, specialised fields and genre. The volume will appeal to researchers interested in language as multidimensional dialogue, particularly with regard to different written specialised texts from different linguistic backgrounds. Novice writers may also find it of help in order to attain a greater understanding of the dialogic nature of writing.